Effect of organic and inorganic fertilizers on faba bean (Vicia faba L.) growth and the response of symbiotic rhizobia with faba bean to some environmental factors in sandy lands - Nazar Nasreldeen Babiker Elnesairi, Mohemed Essalem Emhemed Essalem (Journal of Pure & Applied Sciences, 2020)
This study was conducted to compare the impact of organic fertilizers (chicken and sheep manure) and inorganic fertilizers (urea) and the two factors combined on germination and growth of  two varieties of faba bean plant (local and imported) at the farm of Faculty of Agriculture of the University of Sabha- Libya. Where organic manure was added based on the nitrogen content in chicken manure fertilizer 1.5%, sheep manure 1.24% nitrogen, equivalent to (150 kg nitrogen per hectare) (10 tons/ha) fertilizer of chicken manure and (12.1 tons/ha) fertilizer of sheep manure and the application of inorganic fertilizer Urea (150 kg nitrogen per hectare), in addition to isolating and studying some of the physiological properties of Rhizobia, which are in symbiotic with faba bean plants.The results showed that the addition of mineral nitrogen fertilizer with organic fertilizer together has a significant effect on the number of leaves 65.8% and 96% , length of the plant 12.5% and 11.1% , the fresh weight 91%,101% and dry weight 96% , 99% of the plants of local and imported faba bean plant respectively compared to the control especially the fertilizer of chicken manure, as well as the addition of nitrogen fertilizers and Organic fertilizers individually led to increased growth elements for faba bean plants compared to the control, It also showed that most of the isolates appeared high tolerant to temperatures, as well as the study showed the sensitivity of most isolates to high acidity, as the results also showed that the imported faba bean  are more sensitive to sodium chloride salt than Local faba bean.